STRAWB2 (Stress and Wellbeing After Childbirth): a randomised controlled trial of targeted self‐help materials to prevent post‐traumatic stress disorder following childbirth. (27th February 2020) - Slade, P; West, H; Thomson, G; Lane, S; Spiby, H; Edwards, RT; Charles, JM; Garrett, C; Flanagan, B; Treadwell, M; Hayden, E; Weeks, A
Abstract : Objectives: To test whether providing psychological self‐help materials would significantly lower the incidence of post‐traumatic stress disorder (PTSD) at 6–12 weeks postnatally. Design: Open‐label randomised controlled trial, with blinded outcome assessment. Setting: Community midwifery services in two National Health Service (NHS) trusts in the North West. Sample: A cohort of 2419 women receiving normal NHS postnatal care. Methods: Midwives screened women for traumatic birth experience; 678 women who screened positively (28.1%) were randomly allocated to self‐help with usual care ( n  = 336) or to usual care alone ( n  = 342). The self‐help materials were a leaflet and online film designed to prevent the development of PTSD after trauma exposure through explaining how to manage early psychological responses. Main outcome measure: The primary outcome was a composite of diagnostic and subdiagnostic PTSD at 6–12 weeks postnatally using the gold‐standard Clinician‐Administered PTSD Scale (CAPS‐5) interview. Results: Of the 678 women correctly randomised plus the nine women randomised in error, 478 (70.5%) were followed up. Diagnostic or subdiagnostic PTSD rates at follow‐up did not differ between groups who received self‐help (26.7%, 65/243) or usual care alone (26.2%, 64/244) (intention‐to‐treat analysis: RR 1.02, 95% CI 0.68–1.53). Findings remained consistent in the per‐protocol analysis (RR 1.04, 95% CI 0.85–1.27). Women viewed the materials very positively. There were no adverse effects. Health economic micro‐costing indicated implementation would be very low cost. Conclusions: Many women experience a traumatic birth and risk developing PTSD, but self‐help strategies without professional support are insufficient and should not be routinely introduced. Tweetable abstract: Self‐help information alone does not reduce the number of women developing PTSD after a traumatic childbirth. Tweetable abstract: Self‐help information alone does not reduce the number of women developing PTSD after a traumatic childbirth.